Non-cardioplegic coronary surgery in patients with severe left ventricular dysfunction - Antunes, PE (1999)
OBJECTIVES: Although most surgeons use cardioplegia for myocardial protection during coronary artery bypass grafting (CABG), some still use non-cardioplegic methods with very good early and long-term outcome. However, the results in patients with severe left ventricular dysfunction remain unproved. This study evaluates the perioperative mortality and morbidity in patients with severe left ventricular dysfunction submitted to CABG using non-cardioplegic methods. METHODS: From April 1990 through December 1997, 3,180 patients were consecutively subjected to isolated CABG using non-cardioplegic methods, for construction of the distal anastomoses. This prospective study is based on the 107 (3.4%) patients with severe impairment of the left ventricular function (ejection fraction < 30%). The mean age at operation was 57.0 +/- 9.2 years and 95.3% of patients were male. Fifty three patients (49.5%) were in class CCS III/IV and 12 (11.2%) were subjected to urgent surgery. A history of previous myocardial infarction was recorded in 99 (92.5%) patients. Ninety seven (90.6%) patients had triple vessel and 17 (15.9%) left main stem disease, and 77 (71.9%) had a left ventricular end-diastolic pressure > 20 mmHg. Cardiopulmonary bypass time was 73.1 +/- 21.7 min. The mean number of grafts per patient was 3.2. At least one internal mammary artery was used in all cases and 16 patients (14.9%) had bilateral internal mammary artery grafts (1.2 arterial grafts/patient). Endarterectomies were performed in 23 (21.5%) patients. RESULTS: Perioperative mortality was 2.8% (respiratory-1; cardiac-2). Forty one (38.3%) patients required inotropes, but for longer than 24 h in only 12 (11.2%), and two (1.9%) needed intra-aortic counterpulsation. The incidence of myocardial infarction was 2.8%. Two (1.9%) patients had reintervention for haemorrhage and another five (4.6%) for sternal complications. The incidences of supraventricular arrhythmias, renal failure and cerebrovascular accident were 16.8%, 3.6% and 2.8%, respectively. The mean time of hospital stay was 9.3 +/- 6.4 days. CONCLUSION: These results appear to demonstrate that non-cardioplegic methods afford good myocardial protection and operating conditions with excellent applicability, even in patients with severe left ventricular dysfunction.